The role of PT. Wrestling in Social and Economic Change of the Community in Tokorondo Village, Poso Coastal District, Poso Regency (1976–1996) - Supu, Asmawati; Nuraedah, Nuraedah; Juraid, Juraid; Nongtji, Minarni (Journal of English Language and Education, 2025)
This study aims to describe: (1) the adaptation process of PT. Gulat in Tokorondo Village, (2) the social changes experienced by the Tokorondo community following the presence of PT. Gulat from 1976 to 1996, and (3) the role of PT. Gulat in improving the local economy. The research employed a qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The findings indicate that: (1) the adaptation process of PT. Gulat proceeded swiftly and effectively through collaboration with the community, government, and local institutions; (2) the presence of PT. Gulat led to social transformations, including enhanced social interaction, the emergence of modern ways of thinking, and changes in lifestyle; (3) PT. Gulat contributed to economic improvement by providing employment opportunities, supporting socio-religious activities, and opening new business prospects. Therefore, PT. Gulat played a strategic role in fostering social change while simultaneously improving the living standards of the Tokorondo community during the period of 1976–1996.